Біографічний метод в освітній роботі як аналіз життєвого шляху людини - Шарошкіна, Наталія (Видавництво Львівської політехніки, 2012)
В статье проанализированы способы применения биографического метода в образовательной работе. Акцентируется внимание на анализе жизненного пути методом нарратива. The article analyzes the use of a biographical method in educational work and focuses the attention on the analysis of life’s way by a method of a narrative.
Биографический метод в образовательной работе как анализ жизненного пути человека
Biographical method in educational work as the analysis of life’s way of human
Keywords: биографический метод; нарратив; образовательная деятельность; жизненный опыт; воспоминания; biographical method; narrative; educational activities; life experiences; memories